Chapter 2 Constructing Invisibility The Discursive Erasure of a Black Immigrant Learner in South Africa - Kerfoot, Caroline (Taylor & Francis, 2017)
This chapter analyzes some of the discursive interactions through which a 13-year-old francophone Cameroonian student attempts to construct new social and academic identities. It builds on research on the situated co-construction of micro-interactional identities and macro-social categories such as ethnicity and race. The chapter illustrates the disjunctive interplays of visibility and invisibility that characterize the trajectory of a Cameroonian immigrant student, Aline, as she moves through new diasporic and educational spaces in Cape Town. It examines Aline's gradual invisibilization as an indexical process achieved through a set of inter-related semiotic phenomena such as those identified by Bucholtz and Hall: explicit use of identity labels, implicatures and presuppositions regarding identity positions, and evaluative and epistemic stances in relation to ongoing talk. The chapter also analyzes, first, how stances are interdiscursively achieved or disbarred and, second, how the accretion and/or absence of stances over time have longer lasting consequences, helping to construct more durable social categories.